Eksplorasi Praktik Ramah Lingkungan dan Kinerja Bisnis Berkelanjutan: Studi pada Mebel Uniq Limbah Kayu - Chrisnaldy Widianto; Hani Sirine (CV. Rumoh Aceh Publishing, 2026)
This study aims to analyze the implementation of eco-friendly practices in furniture SMEs at Mebel Uniq Limbah Kayu and their impact on sustainable business performance. The study employs a descriptive qualitative approach with data collection techniques including interviews and surveys. The results indicate that the driving factors of eco-friendly practices include efficient use of raw materials, energy conservation, and business awareness. Meanwhile, the inhibiting factors include cost limitations, lack of knowledge, and market demand conditions. The implementation is carried out gradually through waste utilization and production efficiency, which contributes to improved operational efficiency, customer satisfaction, and business image.